2021
DOI: 10.1186/s12877-021-02404-6
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional scale of perceived social support: evidence of validity and reliability in a Chilean adaptation for older adults

Abstract: Background Given the relevance of social support on the mental health of older adults, having an instrument to evaluate this variable is essential for research in the area. However, mainly, having instruments with suitable evidence of their psychometric properties is critical. For this reason, this study sought to evaluate the factorial and reliability structure of the Multidimensional Scale of Perceived Social Support within autonomous older adults from the Province of Concepción, Chile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
1
9
0
4
Order By: Relevance
“…Only the other fit indices indicated an acceptable fit, thereby displaying some inconsistency in the results. Interestingly, the results of Pérez‐Villalobos et al (2021) showed the same inconsistency in the fit indices.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Only the other fit indices indicated an acceptable fit, thereby displaying some inconsistency in the results. Interestingly, the results of Pérez‐Villalobos et al (2021) showed the same inconsistency in the fit indices.…”
Section: Discussionmentioning
confidence: 89%
“…According to Pérez‐Villalobos et al (2021) who investigated the factorial structure of the MSPSS in home‐dwelling older persons in Chile, previous studies focusing on this target group showed contradictory results, as some of them revealed a two‐factorial structure (Arechabala & Miranda, 2018; Stanley et al, 1998), while others confirmed three factors (Ortiz & Baeza, 2011; Pinto et al, 2014), which was in line with the results of their own study.…”
Section: Introductionmentioning
confidence: 99%
“…For people to use health information appropriately, social support (SS) is crucial. SS refers to the type of help provided to those who need support (Hupcey, 1998), including emotional, instrumental, informational, and evaluative support (Dambi et al, 2018; Pérez‐Villalobos et al, 2021). Among middle‐aged and older adults, SS such as technical support and encouragement from family members and others can promote information and communication technology (ICT) use (Fang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, a grande maioria dos estudos utilizou-se de análises exploratórias, enquanto apenas nove, dentre 70, realizaram análise fatorial confirmatória 9 . As propriedades psicométricas da escala foram estudadas em distintas populações incluindo: adolescentes 12,13 , adultos com doenças crônicas 14,15 , doentes psiquiátricos 16 , pacientes com câncer 17 , idosos 18 e cuidadores de familiares com demência 19 .…”
Section: Introductionunclassified